Duchowe zaślubiny z Boskim Oblubieńcem na podstawie siedemnastowiecznych medytacji norbertańskich - Kaczor-Scheitler, Katarzyna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2012)
This article presents the image of a spiritual wedding between soul-Bride and Divine Bridegroom which is featured in anonymous meditations from the XVII century. They are bunched in manuscript form and stored in the archives of the Sisters of St. Norbert’s Order in Cracow. Therefore, it is proper to make the thesis that the author of this manuscript belonged to this abbey. The primary origin of these meditations is The Song of Songs which shows the special way mystics merge with God. This article also reveals meditations about ”spiritual marriage” that contain visible influences of the Fathers of Church and Żywoty świętych of Piotr Skarga. All these influences are evident not only about the authoress erudition but most of all about her need of strong effect, by means of suggestive images of figures, for the attitude of practitioners of meditations. With the aid of the idea of mutual love between Divine Bridegroom and human being-Bride, meditations were presented standing before God demanding from man spiritual transformation and pose of the human being who desires to internally change yourself for Him.